HUBUNGAN ANTARA TINGKAT KECEMASAN DENGAN SIKLUS MENSTRUASI PADA SISWI KELAS XI JURUSAN AKUNTANSI SMK I PANCASILA AMBULU JEMBER - Sandi Satria (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2015)
Adolescence is a period of transition that connects childhood to adulthood, the physical changes seen in young women that is experiencing the menstrual cycle, one of the causes of menstrual cycle disorders are psychological factors such as anxiety, in Indonesia the number of young women who experience anxiety disorder by 20 %. The purpose of this study was to determine the relationship between the level of anxiety with the menstrual cycle. The method used is analytic correlation with cross-sectional design conducted in May 2014, where the population is all class XI student majoring in accounting SMK I Pancasila Ambulu, sampling technique using probability sampling proportionate to the type of random sampling and obtained 110 student population, 78 as a sample. Methods of data collection using questionnaires. The results of this study using the contingency coefficient association test p value = 0.010 (Ho was rejected sig <0.05) means that there is a significant relationship between the level of anxiety with the menstrual cycle and the value of contingency coefficient = 0.308 correlation is weak but definitely means higher levels of anxiety, the more high menstrual cycle disorders. Irregular menstrual cycles is more common in moderate and severe levels of anxiety. It is recommended to treat anxiety, especially in adolescents by means of support or motivation and knowledge of the wider school education, especially for counseling teachers should pay attention to their students with such anxiety can be overcome in order to maintain reproductive health in adolescents.